The Legal Protection and Responsibility of the Directorate General of Intellectual Property in the Biostime Hong Kong Trademark Dispute - Hosaya Liunda, Sheren Agapena; S.T. Kansil, Christine (State of Islamic Institute Langsa, 2025)
This study aims to analyze the legal protection of the famous Biostime trademark registered by Biostime Indonesia under Law Number 20 of 2016 on Trademarks and Geographical Indications, as well as to examine the responsibility of the Directorate General of Intellectual Property in handling the trademark dispute. The methodology of this research is categorized as normative legal research with legislative, conceptual, and historical approaches. This article uses an analysis of applicable regulations, trademark protection theories, and legal practices in resolving trademark disputes in Indonesia. The findings of this study show that legal protection for famous trademarks in Indonesia needs to be improved to provide better legal certainty for trademark owners, especially in dealing with the registration of similar or identical trademarks. The Directorate General of Intellectual Property, as the responsible institution, must be more careful and thorough in conducting substantive examinations to ensure that no violations occur against famous trademarks that could harm their owners.